Superior Mesenteric Artery-Duodenal Fistula Secondary to a Gunshot Wound. Issue 1 (1st January 2016) - Fielding, Cory M.; Frandah, Wesam; Krohmer, Steven; Flomenhoft, Deborah
Abstract : Arterioenteric fistulas are a rare cause of massive gastrointestinal hemorrhage. We present a patient who developed a fistula between a middle colic artery pseudoaneurysm, a proximal branch of the superior mesenteric artery (SMA), and the third part of the duodenum 2 weeks after a self-inflicted gunshot wound to the abdomen. The patient's presentation, evaluation, treatment, and prognosis are discussed. All prior published cases of SMA-duodenal fistulas are reviewed.